Oil Palm Empty Fruit Bunch (OPEFB) Fiber-Reinforced Acrylic Thermoplastic Composites: Effect of Salt Fog Aging on Tensile, Spectrophotometric, and Thermogravimetric Properties - Valle, Vladimir (2022)
The prioritization of agroindustry fiber wastes as raw materials in development of composites has become a challenge to obtain higher value-added products with targeted applications. In this study, natural fiber-reinforced polymer matrix composites were elaborated using two fiber sizes (605 μm and 633 μm) of oil palm empty fruit bunch (OPEFB) and acrylic thermoplastic resin. In doing so, resin and fibers were mixed at room temperature by maintaining filler content of 42 wt. % for all formulations. In addition, thermomechanical compression moulding was used as composite manufacturing process at four processing temperatures (80, 100, 120, and 140°C). All formulations were subsequently exposed to salt fog spray aging for 330 hours. The effects of accelerated aging process on mechanical, spectrophotometric, and thermogravimetric characteristics were studied. On the whole, results have shown feasibility to use a facile method to elaborate composites based on waterborne acrylic matrix and OPEFB fibers. After salt spray testing, it was observed detectable levels of Aspergillus spp. of fungi in all samples, as a result of phylogenetic organization of microbial activity. Tensile behavior of composites was significantly influenced by processing temperature and fiber size. In broad terms, their overall mechanical properties were improved by the increase of temperature. Additionally, infrared spectroscopy results showed important bands mainly associated to biodegradation of cellulose, hemicellulose, and lignin. On the other hand, two degradation stages were mainly identified in thermogravimetric evaluation. Noteworthy, aging had no significant effect on the thermal properties of composites.